2020
DOI: 10.1002/fsn3.1863
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of migration regularity of phthalates from food packaging materials

Abstract: Phthalate acid esters (PAEs) are one of the essential plastic additives which may lead to plenty of harmful effects, including reproductive toxicity, teratogenicity, and carcinogenicity. Increasing attention has been paid to the migration of plasticizer. In this article, the disposable plastic lunch boxes were taken as the research object. The result showed that dibutyl phthalate (DBP) and diisobutyl phthalate (DIBP) have been mainly found, whose content was 1.5 mg/kg and 2.4 mg/kg, respectively. The LOD was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Several authors show that temperature and contact time increase the migration of phthalates to food [ 39 , 15 , 31 ]. In fact, when the temperature increases, the free energy of the high-energy molecular segment in polypropylene is sufficient to enhance the mobility of PAEs which are low molecular weight substances [ 21 ]. Other studies showed that the storage time was not affect the concentration levels of PAEs in food [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors show that temperature and contact time increase the migration of phthalates to food [ 39 , 15 , 31 ]. In fact, when the temperature increases, the free energy of the high-energy molecular segment in polypropylene is sufficient to enhance the mobility of PAEs which are low molecular weight substances [ 21 ]. Other studies showed that the storage time was not affect the concentration levels of PAEs in food [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 , 17 , 18 , 19 ]. There is an evidence that the migration of phthalates is high in fatty food than is acid or aqueous food [ 20 , 21 ]. In this line [ 10 ], showed that high fat content promotes migration of PAEs into milk packaged in plastic bottles [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For PACs with high boiling points, such as di(2-ethyhexly phthalate) (DEHP) it has been observed that a thin film can form at the surface of the plastic [106], which can facilitate the migration of the chemical from the plastic into dust particles that may have settled on the plastic product. Thus, the diffusion of PACs can result in their potential to leach from the plastic into the surrounding environment either directly through evaporative losses or in relation to the fate of thin films containing PACs forming at the surface of the plastic Chemical leaching rates from different plastic products can be measured and/or estimated based on knowledge of their physicochemical properties, such as their vapour pressure [107][108][109][110]. PACs, however, typically have relatively low vapour pressures, inhibiting the rate of loss due to evaporation.…”
Section: Does Plastic Represent a Source Of Exposure To Plastic-additive Chemicals?mentioning
confidence: 99%
“…As phthalate/bisphenol are small molecules, the available free energy becomes sufficient to enhance migration from the polymer. This free energy obtained by the small molecules (phthalate/bisphenol) increases with temperature and facilitates breaking down the polymer–small molecule interaction forces (Liu et al., 2020). A study by Ayamba et al.…”
Section: Introductionmentioning
confidence: 99%
“…As phthalate/bisphenol are small molecules, the available free energy becomes sufficient to enhance migration from the polymer. This free energy obtained by the small molecules (phthalate/bisphenol) increases with temperature and facilitates breaking down the polymersmall molecule interaction forces (Liu et al, 2020). A study by Ayamba et al (2020) determined that DEHP (4 h contact time into aqueous food simulant) showed migration rising from 0.83 to 1.21 μg/kg as temperature increased from 5 to 80 • C in black PE bags.…”
Section: Introductionmentioning
confidence: 99%